Learning Mandarin Using Multimodal Based Video Media: Learning Mandarin Using Multimodal Based Video Media - Dessy Astutiningtyas; Zuliati Rohmah; Hamama (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
Learning foreign languages, especially Mandarin, is currently being promoted by the Indonesian government. Difficult learning materials make it difficult for students to learn the language. Therefore, teachers are required to be able to choose the right learning media to realize the achievement of learning objectives. With this multimodal-based learning video media, students are expected to be skilled at speaking Mandarin. This type of qualitative descriptive research was conducted in a tertiary institution with 25 Chinese learners at the beginner level as participants. Data was collected using observation in class. Based on the research results, video media can improve students' vocabulary skills.